Theological Reflections on Hans-Georg Gadamer’s Aesthetics - LEGÉNDY , Kristóf (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
In my thesis, my ambition is to put Gadamer’s philosophical hermeneutics at the service of theological thinking; however, not for the sake of a theological argumentation as an end in itself since Gadamer’s aesthetic conception seems to be extremely suitable for correcting the atheistic idea. Gadamer’s aesthetic hermeneutics provides a specific and flexible philosophical framework within which we can move freely, not only for the sake of art but also for the sake of Christian philosophy. My objective, naturally, is to criticize the validity of the atheist idea. I know that our finite and limited concepts are not always sufficient to get to the root of the subject’s particular belief (in this case, atheism), especially since I discuss the reality of aesthetic experience and theological experience, which are by their very nature inexhaustible and infinite intrasubjective aspects as opposed to the quantum structure of concepts. Although the experience of God and the experience of art always avoid theoretical confinement, language enjoys priority in critical thinking and thus has a principled right to be a tool of rational description. Language will not only be the medium but also the goal of my reasoning, which I will define in the triangle of picture–image–language. This will likely point out the inherent flaws and weaknesses of atheist ideas. To quote Gadamer: “Indeed, language often seems ill suited to express what we feel. In the face of the overwhelming presence of works of art, the task of expressing in words what they say to us seems like an infinite and hopeless undertaking.”